Central alpha-adrenergic agonists and need-induced 3% NaCl and water intake - Yada, M. M.; Paula, Patricia Maria de [UNESP]; Menani, José Vanderlei [UNESP]; deLuca, L. A. (Elsevier B.V., 1997)
In the present study, noradrenaline (NOR, alpha-non-specific adrenergic agonist), clonidine (CLO, alpha(2)), phenylephrine (PHE, alpha(1)) or isoproterenol (ISO, beta-agonist) was injected in the medial septal area (MSA) of water-deprived, sodium-deplete or food-deprived rats. NOR (80, 160 nmol) inhibited the intake of 3% NaCl, water deprivation-induced and meal-associated water intake. Food deprivation-induced food intake and 10% sucrose intake were not altered by NOR. CLO (10, 20, 30, 40 nmol) inhibited (80-100% inhibition compared to control during 60 min) the intake of 3% NaCl, water deprivation-induced and meal-associated water intake. CLO had a weaker inhibition on food and 10% sucrose intake (30-50% less than the control during 60 and 15 min, respectively). PHE (160 nmol) inhibited 3% NaCl intake and 10% sucrose intake (30% less than the control for 15-30 min). ISO (160 nmol) did not after water or 3% NaCl intake. NOR induced an increase, CLO and ISO induced a decrease, and PHE no alteration in mean arterial pressure. NOR did not alter water or 3% NaCl intake when injected unilaterally into the caudate nucleus. The results suggest that NOR injected in the MSA acts on alpha(2)-adrenergic receptors inducing a specific inhibition of 3% NaCl and water intake. (C) 1997 Elsevier B.V.
Keywords: noradrenaline; clonidine; phenylephrine; isoproterenol; adrenergic agonists; medial septal area; water intake; salt intake; food intake; blood pressure